The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/eji.1830260534
|View full text |Cite
|
Sign up to set email alerts
|

Induction of T cell unresponsiveness by anti‐CD3 antibodies occurs independently of co‐stimulatory functions

Abstract: Antibodies to the T cell receptor (TcR)-associated CD3 molecules represent potent immunosuppressive agents in vivo in both human and animals models, in spite of their well-characterized mitogenic properties. We demonstrate in this report that antibodies to the B7.2 molecule inhibit IL-2 production in vivo caused by anti-CD3 administration, suggesting that anti-CD3 monoclonal antibodies (mAb) stimulate naive T cells in vivo in a co-stimulation-dependent fashion. To characterize better the mechanisms by which an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…As previously demonstrated by us and others (17,25), anti-CD3 mAb administration in mice led to T cell unresponsiveness to a subsequent in vitro stimulation by soluble anti-CD3 and accessory cells (Fig. 1A).…”
Section: Anti-cd3 Mabs Do Not Induce Naive T Cell Anergy In Vivosupporting
confidence: 84%
See 2 more Smart Citations
“…As previously demonstrated by us and others (17,25), anti-CD3 mAb administration in mice led to T cell unresponsiveness to a subsequent in vitro stimulation by soluble anti-CD3 and accessory cells (Fig. 1A).…”
Section: Anti-cd3 Mabs Do Not Induce Naive T Cell Anergy In Vivosupporting
confidence: 84%
“…As cells were cultured in the absence of exogenous growth factors, a progressive decline in cell viability was observed in control cultures lacking anti-CD3 stimuli. However, culture conditions did not modify the ability of control populations to respond to TCR-mediated stimulations, as cells cultured in the absence of agonists and freshly purified cells responded in similar fashion to receptor triggering (15,25) (data not shown). Therefore, in most experiments, freshly purified CD4 ϩ T cells were used as unstimulated controls.…”
Section: Cell Purifications and In Vitro Treatmentsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are a number of reports of CD4 T cells becoming unresponsive following in vitro or in vivo responses to a variety of stimuli including Mls-1 (43), enterotoxin (44), and mitogenic anti-CD3 (45). In experiments examining in vivo and in vitro stimulation with anti-CD3 mAb Andris et al (45) showed that unresponsiveness developed even when the initial response included a contribution from CD28-dependent costimulation.…”
Section: Discussionmentioning
confidence: 99%
“…(Manassas, VA, U.S.A.). The I-E k -restricted, pigeon cytochrome-c-specific T-cell hybridoma 3B4 (CD90 + , CD3 + , CD4 + , CD8 − ) was derived by Dr. Fabienne Andris [22]. Murine astrocytes were purified as described in [23].…”
Section: Cell Linesmentioning
confidence: 99%